Caracterização da resistência genética na cultivar andina de feijão comum Amendoim Cavalo ao Colletotrichum lindemuthianum - Nanami, Danielle Sayuri Yoshida (2014)
Anthracnose, caused by Colletotrichum lindemuthianum (Sacc. and Magnus) Briosi and Cavara, is one of the most important fungal disease of common bean an efficient method to control this disease is the use of resistant cultivars. Thus, a continuous search of new resistance sources is necessary. Previously studies conducted in our laboratory revealed that Andean cultivar Amendoim Cavalo is resistant to races to races 2, 7, 65, 73, 89 and 2047 of the anthracnose pathogen used in this study. The objective of this work was to characterize the genetic resistance to anthracnose in Amendoim Cavalo using inheritance and allelism tests. The experiment was conducted in green house and at Laboratório de Melhoramento de Feijão Comum e de Biologia Molecular do Núcleo de Pesquisa Aplicada à Agricultura (Nupagri). The results of inheritance tests in F2generation os Amendoim Cavalo × México 222 and Amendoim Cavalo × PI 207262 crosses, inoculated with 73 and 2047 races, respectively, set the ratio 3R:1S, proving the action of a single dominant gene in Amendoim Cavalo cultivar. The allelism tests demonstrated that the dominant gene present in Amendoim Cavalo is independent from the genes previously characterized and from the genes present in the cultivars Paloma, Perla and Jalo Pintado 2. The authors propose the Co-19 symbol to designate the new resistant gene to C. lindemuthianum. The results show high contribution to breeding programs, once Amendoim Cavalo cultivar can be considered an important Andean source of resistance to C. lindemuthianum.